Nordiska högskolan för Folkhälsovetenskap (NHV) ett nordiskt utbildnings- och Kunskapscentrum för Folkhälsovetenskap - Ringsberg, Karin C; Thorpenberg, Stefan (Socialmedicinsk tidskrift, 2025)
Nordiska högskolan för folkhälsovetenskap (NHV), en institution på universitetsnivå som lyder under Nordiska ministerrådet, har en lång erfarenhet av utbildning och kunskapsspridning av folkhälsovetenskap. I den här artikeln presenteras NHV:s uppdrag och inriktning med fokus på forskning, forskarutbildning samt dess specifika roll som ett Nordiskt Kunskapscentrum för Health Promotion. Unique knowledge is collected at the Nordic school of public health (NHV) regarding public health in the five Nordic countries. Students as well as teachers/researchers are recruited from all the Nordic countries. There are ongoing efforts made to strengthen research activities between the Nordic countries, especially within the fields of health promotion and the Nordic Research Academy in Mental Health. The establishment of the Knowledge Center for health promotion provides unique possibilities to further deepen this work. A pilot study recently performed within the Nordic research network for health promotion shows that fields that should be given priority to be studied from a health promotion perspective are the health of children and elderly, different aspects of inequality in health, methods used to evaluate studies and projects and cooperation between researchers, practitioners, politicians and journalists. It is also important to compare Nordic health promotive work with what such a work is done in Europe and globally.